PENYUKIA (PENYULUHAN DAN EDUKASI KESEHATAN IBU DAN ANAK) PADA PUSKESMAS RAWAMERTA KARAWANG - Hilmi, Indah Laily; Salman, Salman; Sholih, Mally Ghinan; Ratnasari, Devi; Septiani, Dia (Transpublika Publisher, 2022)
The knowledge of maternal and child health and nutrition in Sukamerta Village is highlighted in the context of community well-being. The limited understanding of this issue has led to the need for interventions aimed at raising awareness of the importance of health aspects. This study aims to provide sustainable solutions through counseling and education efforts at Rawamerta Community Health Center. The research method applied includes a series of systematically designed steps. Starting from pre-event questionnaire filling to evaluate the initial level of knowledge, direct counseling, educational video screenings, interactive question and answer sessions, and distribution of brochures as additional sources of information. This approach not only delivers information but also encourages active participation of participants to enhance the effectiveness of knowledge transfer. The research results show a significant improvement in understanding of maternal and child health and nutrition after participating in the educational event. The success of the counseling, reaching a rate of 86.78%, confirms that this approach has a strong positive impact on enhancing community knowledge regarding crucial health issues.